2009
DOI: 10.1007/s11745-009-3379-2
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Fat Exacerbates Weight Gain and Obesity in Female Liver Fatty Acid Binding Protein Gene‐Ablated Mice

Abstract: Since liver fatty acid binding protein (L-FABP) facilitates uptake/oxidation of long-chain fatty acids in cultured transfected cells and primary hepatocytes, loss of L-FABP was expected to exacerbate weight gain and/or obesity in response to high dietary fat. Male and female wild-type (WT) and L-FABP gene-ablated mice, pair-fed a defined isocaloric control or high fat diet for 12 weeks, consumed equal amounts of food by weight and kcal. Male WT mice gained weight faster than their female WT counterparts regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 65 publications
8
73
1
5
Order By: Relevance
“…Although LCFA oxidation is decreased, the LFABPnull mouse nevertheless does not develop hepatosteatosis following a high fat diet, indicating protection against development of the metabolic syndrome (2, 39 -41); however, others have reported an exacerbation of obesity (42). Recently, it was shown that LFABP-null mice were highly susceptible to the development of cholesterol gallstones, with the effect likely secondary to increased liver cholesterol levels and increased enterohepatic bile acid pool size (43).…”
Section: Tissue-specific Fabp Functionsmentioning
confidence: 99%
“…Although LCFA oxidation is decreased, the LFABPnull mouse nevertheless does not develop hepatosteatosis following a high fat diet, indicating protection against development of the metabolic syndrome (2, 39 -41); however, others have reported an exacerbation of obesity (42). Recently, it was shown that LFABP-null mice were highly susceptible to the development of cholesterol gallstones, with the effect likely secondary to increased liver cholesterol levels and increased enterohepatic bile acid pool size (43).…”
Section: Tissue-specific Fabp Functionsmentioning
confidence: 99%
“…Регулирующее действие алиментарных жиров на метаболизм липидов реализуется на уровне модуляции экспрессии особых факторов транскрипции, участвующих в метаболизме жирных кислот -PGC-1b (peroxisome-proliferatoractivated receptor-gamma co activator 1 beta), HNF4 (hepatocyte nuclear factor 4), PPAR (peroxisome proliferator-activated receptor), SREBP1 (sterol regulatory element-binding protein) [7][8][9]. Этот механизм опосредуется через активацию ферментов элонгаз, осуществляющих удлинение цепи насыщенных жирных кислот, а также D9 десатуразы, превращающей насыщенные жирные кислоты в моноеновые.…”
Section: Introductionunclassified
“…Изменение липидного обмена в печени под влиянием алиментарных факторов могут быть отражены и в трансформации состава жирных кислот липидов плазмы крови, мембран клеток периферических органов, в частности эритроцитов [9,10].…”
Section: Introductionunclassified
See 2 more Smart Citations